Monitoring Student Interaction during Collaborative Learning: Design and Evaluation of a Training Program for Pre-Service Teachers. (March 2016) - Kaendler, Celia; Wiedmann, Michael; Leuders, Timo; Rummel, Nikol; Spada, Hans
The monitoring by teachers of collaborative, cognitive, and meta-cognitive student activities in collaborative learning is crucial for fostering beneficial student interaction. In a quasi-experimental study, we trained pre-service teachers ( N  = 74) to notice behavioral indicators for these three dimensions of student activities. Video clips of student interactions in collaborative learning settings served as learning opportunities in the training and as test scenarios for measuring monitoring competency in an assessment tool. Participants completed the assessment tool before and immediately after the training program. A control group ( N  = 33) completed the assessment tool twice but did not receive training in between. Results show that monitoring competency increased significantly in the training group but not in the control group. This provides initial evidence that a video-based training program can effectively enhance pre-service teachers' noticing of behavioral indicators of collaborative, cognitive, and meta-cognitive student activities in a relatively short time. Our findings are of practical relevance as evaluating student interactions in a collaborative learning setting is challenging, yet also a skill much needed in teacher practice.